Pengaruh Pendapatan Asli Daerah, Dana Perimbangan, dan Dana Pembiayaan terhadap Kemiskinan di Kabupaten Purbalingga - Teguh Priyono; Abdul Aziz Ahmad; Lilis Siti Badriah (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Fiscal decentralization is an implementation of regional autonomy, where fiscal decentralization provides space for regional governments to develop the regional economy, including alleviating poverty by utilizing regional financial tools. The aim of this research is to analyze the influence of local revenue, balancing funds and financing funds on poverty. This research uses secondary data with time series data for the period 2007-2022. This research uses multiple regression analysis techniques (Ordinary Least Square). Based on the results of the analysis, it shows that local original income and balancing funds have a negative and significant effect on poverty. Meanwhile, financing funds have no effect on poverty in Purbalingga Regency.